2014
DOI: 10.1007/s00192-014-2471-1
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Burch colposuspension: a surgical case and instructional video

Abstract: Robotic Burch colposuspension can be completed in a safe and effective manner and should be considered as an option for patients in whom an anti-incontinence procedure is indicated and who are already undergoing robotic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 1 publication
0
11
0
1
Order By: Relevance
“…Most of the reported data showed similar cure rates (62% to 100%) between laparoscopic Burch operation and open surgery [73][74][75]79]. Robotic surgery is also an emerging technique for cystocele repair [76,77]. Daneshgari et al [76] reported the robotic abdominal sacrocolpopexy or sacrouteropexy repair of POP on the basis of POP-Q stage.…”
Section: ) Minimally Invasive Laparoscopic and Robotic Popmentioning
confidence: 97%
See 1 more Smart Citation
“…Most of the reported data showed similar cure rates (62% to 100%) between laparoscopic Burch operation and open surgery [73][74][75]79]. Robotic surgery is also an emerging technique for cystocele repair [76,77]. Daneshgari et al [76] reported the robotic abdominal sacrocolpopexy or sacrouteropexy repair of POP on the basis of POP-Q stage.…”
Section: ) Minimally Invasive Laparoscopic and Robotic Popmentioning
confidence: 97%
“…However, the advantages of minimally invasive surgery, which include improved cosmetic aspects, reduced pain, short recovery time, low morbidity, and convenience of surgery, have led surgeons to perform more laparoscopic-based surgery in the field of POP. Most reports that compared open, laparoscopic, and robotic POP surgeries with one another showed similar outcomes in cure rate, anatomic results, and complications [16,[67][68][69][70][71][72][73][74][75][76][77][78]. From the aspect of satisfaction with the operation, minimally invasive surgery showed a higher rate of satisfaction [78].…”
Section: ) Minimally Invasive Laparoscopic and Robotic Popmentioning
confidence: 99%
“…Recently, the technique has had a resurgence following the well-publicised problems with transvaginal mesh. Robotic Burch colposuspension was first described by Francis and coworkers [38] in 2015, and another case report was published by Bora and colleagues [39] in 2017. Apart from these isolated case reports, the evidence is very limited; a pilot study of 20 patients compared robotic hysterectomy and robotic colposuspension with open hysterectomy and colposuspension [40].…”
Section: Bladder Neck Reconstructionmentioning
confidence: 99%
“…Francis et al ., have published an instructional video in the July issue of International Urogynecological Journal regarding the safety and feasibility of robotic Burch colposuspension as an anti incontinence surgery. [ 65 ]…”
Section: Burch Colposuspensionmentioning
confidence: 99%